Audit in Change: An Analysis of the EU Audit Reform on Statutory Audit for the Case of Germany - Maier,Lisa; Warkotz,Laura (2015)
The purpose of this paper is to add knowledge to the understanding in which way the measures of the audit reform are in accordance with the EC’s intended objectives. This is examined for the case of Germany. The study further contributes to the program impact theory by applying this theory to a new research area.
Keywords: EU Audit Reform; Germany; Program Impact Theory; Regulation (EU) 537/2014; Directive 2014/56/EU